Communication strategies used by adult male and female ESL speakers in same-gender and cross-gender interactions - Kho, Diana Tiee Pai (Universiti Malaysia Sarawak (UNIMAS), 2006)
The study aims at investigating communication strategy (CS) use of male and female adult ESL speakers in tertiary setting. The objectives are to find out the use and preference in terms of CS used, CS use in same-gender and cross-gender pairs, and the purpose of using CS. Two discussion questions were used to obtain interactional data from 20 ESL speakers, one for the same-gender pairs and another for cross-gender pairs. The 20 transcripts were analysed based on the combination of psychological perspective (Faerch & Kasper, 1984), social interaction viewpoint (Tarone, 1981), and discourse perspective (Clennell, 1995). Then frequency counts and percentages were prepared as the descriptive statistics for this study. The results showed that from the total number of CS (n=453), generally male and female ESL speakers had similar preference for CS use but female speakers (n=260) used more CS than male speakers (n=193) in general except for approximation and topic avoidance. Male speakers used more repetition, message abandonment, and topic fronting in same-gender pairs, while female speakers used more topic fronting and approximation in cross-gender pairs. As to the question of the purpose of CS use, most of them were used for overcoming language deficiency (66%), followed by message enhancement (28%) and lastly avoidance (6%). In addition, since female speakers used more CS generally, therefore female speakers were found to use more strategies for every purpose compared with the male speakers. Out of the total number of CS used for each purpose, female speakers used 56% of overcoming language deficiency, 60% of message enhancement, and 60% of avoidance.